Visuo-spatial imagery in dreams of congenitally and early blind: a systematic review - Ilic, Katarina; Bertani, Rita; Lapteva, Neda; Drakatos, Panagis; Delogu, Alessio; Raheel, Kausar; Soteriou, Matthew; Mutti, Carlotta; Steier, Joerg; Carmichael, David W.; Goadsby, Peter J.; Ockelford, Adam; et al. (Frontiers in Integrative Neuroscience, 2023)
The presence of visual imagery in dreams of congenitally blind people has long been a matter of substantial controversy. We set to systematically review body of published work on the presence and nature of oneiric visuo-spatial impressions in congenitally and early blind subjects across different areas of research, from experimental psychology, functional neuroimaging, sensory substitution, and sleep research.Methods: Relevant studies were identified using the following databases: EMBASE, MEDLINE and PsychINFO.Results: Studies using diverse imaging techniques and sensory substitution devices broadly suggest that the "blind" occipital cortex may be able to integrate non-visual sensory inputs, and thus possibly also generate visuo-spatial impressions. Visual impressions have also been reported by blind subjects who had near-death or out-of-body experiences.: Deciphering the mechanistic nature of these visual impression could open new possibility in utilisation of neuroplasticity and its potential role for treatment of neurodisability.